1997
DOI: 10.1002/(sici)1099-1085(199709)11:11<1475::aid-hyp480>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling runoff using optical satellite remote sensing data in a high mountainous alpine catchment of Italy

Abstract: Development of hydrological models for seasonal and real-time runo forecast in rivers of high alpine catchments is useful for management of water resources. The conceptual models for this purpose are based on a temperature index and/ or energy budget and can be either lumped or distributed over the catchment area. Remote sensing satellite data are most useful to acquire near real-time geophysical parameters in order to input to the distributed forecasting models. In the present study, integration of optical sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…To describe significant heterogeneity of temperature, precipitation, snow, and glacier, distributed hydrological models are generally used for precipitation-runoff modeling in mountain regions (Daly et al, 2000;Klok et al, 2001). Also, the utilization of remote-sensing products of precipitation and snow cover data in mountain runoff modeling has become more popular in recent years (Swamy and Brivio, 1997;Akyurek et al, 2011;. Most of these studies report sound simulation results.…”
Section: Z H He Et Al: Diagnostic Calibration Of a Hydrological Modelmentioning
confidence: 99%
“…To describe significant heterogeneity of temperature, precipitation, snow, and glacier, distributed hydrological models are generally used for precipitation-runoff modeling in mountain regions (Daly et al, 2000;Klok et al, 2001). Also, the utilization of remote-sensing products of precipitation and snow cover data in mountain runoff modeling has become more popular in recent years (Swamy and Brivio, 1997;Akyurek et al, 2011;. Most of these studies report sound simulation results.…”
Section: Z H He Et Al: Diagnostic Calibration Of a Hydrological Modelmentioning
confidence: 99%
“…There has been much written regarding the potential for improving snowmelt estimation and the subsequent streamflow forecasts through better estimates of initial states and the use of advanced models and data products (Perkins, 1988;Day et al, 1989;Swamy and Brovio, 1997;Marks et al, 1999;Carroll et al, 2001;Walter et al, 2005;Shamir and Georgakakos, 2006;Lehning et al, 2006). The National Weather Service (NWS), responsible for short-and longterm streamflow predictions across the United States, uses the SNOW17 model (Anderson, 1973) as part of their river forecast system.…”
Section: Introductionmentioning
confidence: 99%
“…The SRM accepts either the daily mean temperature (T avg ) or the average of the daily maximum temperature (T max ) and the daily minimum temperature (T min ), while using measured data directly is generally unreasonable. Swamy [10] calculated several values for T avg through various combinations of hourly observed data, and the simulation study indicated that using the average of measured T max and T min led to a decrease in accuracy during some periods. In order to obtain the representative basin mean temperature, Richard et al [9] attempted different weighting methods for data collected from several stations and showed that different temperature inputs may cause a large difference [9] .…”
Section: Estimation Of Temperaturementioning
confidence: 99%
“…Thus, it is necessary that the measured data should be representative of the altitude. As in earlier research work, the measured data can be directly used by the model when the gauge stations are sufficient or the basin area is very small [9][10][11] .…”
mentioning
confidence: 99%